Cicerina debrae n. sp. (Platyhelminthes: Kalyptorhynchia, Cicerinidae) from the Southern Atlantic Coast, USA - Tucker, Kea (Zootaxa, 2014)
Cicerina debrae is described as a new species of kalyptorhynch flatworm belonging to the Cicerinidae. This species was found in surface sediment from the lower half of the beach at two sites in North Carolina and is identical to museum material previously collected from North Carolina and from the Atlantic coast of Florida. C. debrae differs from its congeners in the shape of the ductus spermatici and the copulatory cirrus.